Mood disturbances following increased training in swimmers - Morgan, W. P.; Costill, D. L.; Flynn, M. G.; Raglin, J. S.; O'Connor, P. J. (Medicine & Science in Sports & Exercise, 1988)
Twelve male swimmers were assessed prior to, during, and after increasing workloads from 4,000 m to 9,000 m at 94% VO2max over a 10-day period. Swimmers completed a POMS, muscle soreness scale, and 24-hour history each morning prior to starting the first of two daily training sessions. Significant increases occurred in ratings of exercise intensity, muscle soreness, depression, anger, fatigue, and global mood disturbance, along with a reduction in general sense of well-being. Close agreements (89%) were found between psychological and physiological measures of the stress response. Many of the physiological and psychological responses tended to level-off after the first five days of exposure to the training stress. This suggested adaptation. However, three of the subjects failed to accommodate the strain of training. In those subjects, the psychological changes were very marked. It was concluded that significant psychometric changes occur over a 10-day intense training period. Those changes resemble alterations observed in swimmers exposed to increased training across several months. Mood states may be a sensitive method for evaluating the onset of staleness in serious athletes.